Kontribusi Peran Perempuan dalam Pengelolaan Usaha Budidaya dan Penanganan Pasca Panen Rumput Laut di Pulau Nusa Penida, Kecamatan Nusa Penida, Kabupaten Klungkung, Propinsi Bali - Taryono . (Buletin Ekonomi Perikanan, 2004)
Balinese women had significant role in their rural economies. In many cases, moreover, they also worked in the hard duties, such as construction worker. According to rural economies, the seaweed culture had become major activities for coastal communities in Nusa Pen ida Island, since a long time ago. This research was dedicated to analyse the women's role in those activities. The more detail analysis was developed to understand their role in the seaweed culture management including planning step, post harvest handling, marketing process and managing profit of the business. Eventually, the results of the research brought up the clearly evidence of the significant role of the Balinese women in the all management steps of the coastal seaweed culture in the Nusa Pen ida Island.